Toxicity of Antioxidant Supplements in Patients with Male Factor Infertility: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Massimiliano Creta; Davide Arcaniolo; Giuseppe Celentano; Luigi Napolitano; Roberto La Rocca; Marco Capece; Gianluigi Califano; Francesco Mangiapia; Lorenzo Spirito; Felice Crocetto; Ciro Imbimbo; Nicola Longo; et al. (MDPI AG, 2021)
Treating oxidative stress through antioxidant therapy has been considered an appealing strategy in the management of male infertility. However, evidence regarding the toxicity of antioxidant therapy is controversial. We summarized the available clinical evidence on the toxicity associated with the use of antioxidants in infertile males. A systematic review was performed in March 2021. We included randomized controlled trials evaluating the incidence of adverse events in male patients with infertility receiving antioxidant therapy. Thirteen studies involving 1999 male patients were identified. Antioxidant supplementation in patients with male factor infertility was associated with a statistically significantly increased risk of nausea (Odds Ratio: 2.16, 95% Confidence Interval: 1.05-4.43, p = 0.036), headache (Odds Ratio: 3.05, 95% Confidence Interval: 1.59- 5.85 p = 0.001), and dyspepsia (Odds Ratio: 4.12, 95% Confidence Interval: 1.43-11.85, p = 0.009) compared to a placebo. Treatment discontinuation due to adverse events was not significantly higher in patients taking antioxidants compared to a placebo (Odds Ratio: 2.29, 95% Confidence Interval: 0.76-6.88, p = 0.139). When antioxidant supplementation is considered, a more accurate risk/benefit analysis is warranted.